2015
DOI: 10.1111/imre.12108
|View full text |Cite
|
Sign up to set email alerts
|

How Migrant Status Affects Health beyond Socioeconomic Status: Evidence from Austria

Abstract: The debate on health inequalities usually focuses on the interplay between socioeconomic status (SES) and health, where it is widely accepted that the former influences the latter. However, little is known on whether the influence of SES on health is sufficient to explain the observed lower health statuses among various migrant groups in European countries. This paper presents a model that integrates the influences of SES and migrant status on health and tests its implications empirically for Austria. Several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Furthermore, socioeconomic characteristics likely have differential effects on the health of migrants depending on the culture and area of origin, 43 which could modify our results. Some new neighbourhoods in China, especially in Shenzhen, are composed of groups of migrants of similar ages, originating from the same areas, and living in small areas such as dormitories 44 where high social cohesion could influence mental health outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, socioeconomic characteristics likely have differential effects on the health of migrants depending on the culture and area of origin, 43 which could modify our results. Some new neighbourhoods in China, especially in Shenzhen, are composed of groups of migrants of similar ages, originating from the same areas, and living in small areas such as dormitories 44 where high social cohesion could influence mental health outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…Refugee 1 migration and integration have become prominent topics in research (Brell, Dustmann, and Preston 2020;Hatton 2020) and politics in recent years (OECD 2018), as migration figures have increased in response to war, persecution, and other forms of violent conflicts associated with events like the Arab Spring in late 2010 (Hatton 2020;Valdez 2020). The often life-threating events and stressful or traumatic experience that refugees encounter before and during forced migration (Brücker, Jaschke, and Kosyakova 2019), together with substandard living conditions and post-migration stress in host countries (Silove et al 1999;Robjant, Hassan, and Katona 2009), create a specific burden for refugees compared to other migrants, particularly vis-à-vis health status (see Lindert et al 2009;Sardadvar 2015). Especially common among refugees are mental health problems (Silove et al 2007;Li, Liddell, and Nickerson 2016;Claassen and Jäger 2018;Kindermann et al 2020) that can be difficult to detect in this population due to cultural and linguistic barriers, as well as communication and recall problems (Crumlish and O'Rourke 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on internal migrants provide inconsistent and scarce results. Studies using data from some high-income countries (e.g., Austria and the European Union) strengthened the evidence linking a lower socioeconomic status with poor health outcomes, whereas evidence from studies conducted in the US and Peru showed that individuals having low socioeconomic status had similar or better health than that of their richer and more acculturated counterparts [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%